Pembelajaran IPA terintegrasi TaRL-SEL dengan PBL dalam meningkatkan hasil belajar, berpikir kritis, & sosial-emosional - Putri, Raden Roro Risang Ayu Dewayani; Winingsih, Puji Hariyati; Setyorini, Sulis; Zusroni, Agus (Indonesian Journal of Learning and Educational Studies, 2024)
TaRL (Teaching at the Right Level)-SEL (Social Emotional Learning) integrated science learning facilitates students' learning needs, optimises cognitive development and social-emotional domain in CASEL competency framework. This class action research was conducted in class VIII C SMP N 1 Sedayu including pre-cycle, cycle 1, cycle 2, cycle 3, and cycle 4. The research data was analysed descriptively quantitatively. TaRL integrated SEL with PBL model can improve students' learning outcomes, from 56.25% completeness in the pre-cycle to 96.87%. The improvement of learning outcomes is related to the learning process and learning climate according to the needs of students. The learning process is linked to various things closest to the learner's environment including adapting the local potential of D.I. Yogyakarta. The percentage of completion of critical thinking skills increased from pre-cycle 31.25% to the last cycle 100%. The increase is related to the variety of learning that is done. Learning process activities with discussions/case studies, laboratory experiments, and product manufacturing improved critical thinking and CASEL competence. Self-awareness from moderate category 42.19% increased to very high category 83.31%. Self-management from moderate category 42.81% increased to high category 80.34%. Social-awareness increased from low category 40.31% to very high category 83.94%. Relationship-skills increased from low 39.38% to very high 82.38%. Responsible-decision making increased from a low category of 40.94% to a very high category of 84.50%.